The biological effect of orange (Citrus sinensis L.) by-products on metabolic biomarkers: A systematic review - Pineda-Lozano, Jessica Elizabeth; Fonseca-Bustos, Verónica; Martinez-Moreno, Alma Gabriela; Virgen-Carrillo, Carmen Alejandrina (Frontiers in Sustainable Food Systems, 2022)
Industrial processing of citrus fruits generates an important amount of wastes that evoque environmental damage. Orange is the main citrus consumed worlwide and after its use, approximately more than a half of the fruit remains as by-products with important content of bioactive compounds, usefull for the development of promising nutraceuticals for the treatment of non-communicable diseases. From a systematic review, this study aimed to gather scientific evidence about the biological effects of orange by-products. 14 studies carried out in rodent models in the last 10 years were retrieved from PubMed and ScienceDirect databases. From eligibility criteria, none human study was identified. Further, studies that used another animal species, used another type of citrus, or used a combination of orange with other citrus were excluded. After assessed the risk of bias by SYRCLE´s RoB tool, the synthesis of results was shown in an informative table, with which it was determined that the most of the studies used a pathological model of chronic diseases; the peel was the most used agri-food by-product and the effect was the reduction in levels of triglycerides, total cholesterol, HDL-cholesterol glucose and systolic blood pressure in the groups exposed to orange. However, to assess what will happen clinically, these results need to be tested in the future in human clinical trials. The studies collected on the use of orange by-products strengthen the global sustainable food agenda. It is important to consider new research directions about the use of citrus fruit residues, since it not only impacts the problem of its disposal, but also provides solutions to eliminate the resulting contamination.